1998
DOI: 10.1086/305791
|View full text |Cite
|
Sign up to set email alerts
|

The Characteristics of Millisecond Pulsar Emission. II. Polarimetry

Abstract: We have made polarimetric monitoring observations of most of the millisecond pulsars visible from the northern hemisphere at 1410 MHz over a period of three years. Their emission properties are presented here and compared with those of normal pulsars. Although we demonstrated in paper I that millisecond pulsars exhibit the same flux density spectra and similar profile complexity, our results presented here suggest that millisecond pulsar profiles do not comply with the predictions of classification schemes bas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
137
10

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(173 citation statements)
references
References 67 publications
(133 reference statements)
26
137
10
Order By: Relevance
“…In Figure 7b we present the proÐle resulting from 330 minutes of observations acquired on 4 separate days and at a wide range of orbital phases ; these averaged data yield a maximum linear polarization of 9%. Our observations do not support the result of Xilouris et al (1998), who found a linear polarization fraction of 60%. The data of Xilouris et al (1998) were taken during a single observing session (K. M. Xilouris 1998, private communication) ; although we saw no similar results in our 4 daysÏ observations, it is possible that the linear polarization of 1744[24 is variable.…”
Section: Psr B1744[24acontrasting
confidence: 99%
See 4 more Smart Citations
“…In Figure 7b we present the proÐle resulting from 330 minutes of observations acquired on 4 separate days and at a wide range of orbital phases ; these averaged data yield a maximum linear polarization of 9%. Our observations do not support the result of Xilouris et al (1998), who found a linear polarization fraction of 60%. The data of Xilouris et al (1998) were taken during a single observing session (K. M. Xilouris 1998, private communication) ; although we saw no similar results in our 4 daysÏ observations, it is possible that the linear polarization of 1744[24 is variable.…”
Section: Psr B1744[24acontrasting
confidence: 99%
“…There is considerable overlap between the present set of pulsars and those studied by Xilouris et al (1998) at 1410 MHz using the 100 m telescope at E †elsberg, Germany ; our study provides a needed complement to these higher frequency observations. Recently, Sallmen (1998) has studied several of the pulsars presented here, conducting observations at the National Radio Astronomy Observatory, Green Bank, WV, and E †elsberg, Germany.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations